DETERMINANTS OF EARNINGS MANAGEMENT IN CONSUMER SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FROM 2021 TO 2023: INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE - Yoselin Yoselin; Indra Widjaja (Graduate Program of Universitas Tarumanagara, 2025)
This study aims to examine the effect of managerial ownership, board size, audit committee, and board diversity on earnings management, with institutional ownership acting as a moderating variable. The study focuses on company’s sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Using a quantitative approach through purposive sampling, a total of 168 company-year observations were analyzed using EViews 12. The findings show that managerial ownership does not have a substantial effect on earnings management, while board size, audit committee, and board diversity show a significant positive relationship with earnings management. In summary, institutional ownership weakens the relationship between board size, audit committee, and board diversity with earnings management, but fails to moderate the effect of managerial ownership. This study drwas attention to strong institutional ownership, which enhances the effectiveness of corporate governance mechanisms and reduces distortions in financial reporting caused by profit manipulation practices.